2019
DOI: 10.1016/j.ajog.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent pregnancy outcomes after open maternal-fetal surgery for myelomeningocele

Abstract: Background: Open maternal-fetal surgery (OMFS) for fetal myelomeningocele (fMMC) results in reduction in neonatal morbidity related to spina bifida but may be associated with fetal, neonatal, and maternal complications in subsequent pregnancies. Objective:The objective of this study was to ascertain obstetric risk in subsequent pregnancies after OMFS for fMMC closure.Study Design: An international multicenter prospective observational registry created to track and report maternal, obstetric, fetal/neonatal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 24 publications
(19 reference statements)
3
54
3
Order By: Relevance
“…The live born rate for those progressing beyond 20 weeks was 96.2% and median gestational age at delivery was 37 weeks. Nevertheless, the risk of uterine dehiscence/thinning (17.3%) and uterine rupture in subsequent pregnancies was significant (9.6%) and resulted in a fetal death prevalence of nearly 4% …”
Section: Maternal Outcomesmentioning
confidence: 96%
“…The live born rate for those progressing beyond 20 weeks was 96.2% and median gestational age at delivery was 37 weeks. Nevertheless, the risk of uterine dehiscence/thinning (17.3%) and uterine rupture in subsequent pregnancies was significant (9.6%) and resulted in a fetal death prevalence of nearly 4% …”
Section: Maternal Outcomesmentioning
confidence: 96%
“…Fetal therapy contributes significantly to the literature, and this year we highlight maternal issues as well as technological developments that could enhance our ability to deliver in‐utero therapy. In 2019, two papers described the potential maternal complications of fetal surgery . The first was a systematic review of 166 studies reporting either open or endoscopic in‐utero surgery.…”
Section: Advances In Fetal Theraphymentioning
confidence: 99%
“…This is in contrast to the second study that reported maternal outcomes for 77 women undergoing hysterotomy for fetal spina bifida repair. Here they showed that the risk for rupture (9.6%) and perinatal death was similar to that seen after classical caesarean section . This is an important driver in the further development of endoscopic techniques.…”
Section: Advances In Fetal Theraphymentioning
confidence: 99%
“…However, despite its beneficial effects, open prenatal SBR as it is performed today is less than perfect. Not only is it associated with maternal and fetal risks (Adzick et al, ; Goodnight et al, ; Johnson et al, ), but also results are not consistent. Therefore, future improvements, especially regarding operation techniques and timing, are warranted.…”
Section: Introductionmentioning
confidence: 99%